2010
DOI: 10.1002/cncr.25479
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the GeneSearch breast lymph node assay for the rapid evaluation of sentinel lymph nodes in breast cancer

Abstract: BACKGROUND:The potential for reducing the need for second surgery for axillary lymph node dissection (ALND) has made the intraoperative evaluation of sentinel lymph nodes (SLNs) attractive. The goal of the current study was to evaluate the clinical application of the breast lymph node (BLN) assay, a real-time reverse transcriptase-polymerase chain reaction assay for SLN metastases, by comparing this test with routine pathologic examination. METHODS: A total of 117 patients with breast cancer underwent breast s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
0
10
0
2
Order By: Relevance
“…The authors also noted the possibility of false positive results (4% in their experiments). Funasako et al obtained very similar results for detecting all me-tastases (95.7% sensitivity for metastases larger than 2 mm, 60% for micrometastases and 55.6% for ITC) [12]. Mansel et al reported 88.9% sensitivity using GeneSearch BLN Assay [21].…”
Section: Discussionmentioning
confidence: 87%
“…The authors also noted the possibility of false positive results (4% in their experiments). Funasako et al obtained very similar results for detecting all me-tastases (95.7% sensitivity for metastases larger than 2 mm, 60% for micrometastases and 55.6% for ITC) [12]. Mansel et al reported 88.9% sensitivity using GeneSearch BLN Assay [21].…”
Section: Discussionmentioning
confidence: 87%
“…When only CK19 and MG were included as parameters the sensitivity of the BLN assay decreased from 81.1 % to 73.0 % and 51.4 %, respectively [18]. However, RT-LAMP was reported as more sensitive than the PCR method [23].…”
Section: Discussionmentioning
confidence: 97%
“…Among these methods, the Food and Drug Administration (FDA) approved breast lymph node (BLN) assay and the fully automated GeneXpert assay are all based quantitative reverse-transcription PCR (QRT-PCR) and can be completed in approximately 30-40 min. Unfortunately, despite their good performance compared to pathological examination [15][16][17][18][19][20][21], the two methods have not been widely applied in clinical practice because the BLN assay was withdrawn from the market [14], and the GeneXpert assay is not commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Dans la situation du GS associé au geste mammaire sous AG, le risque de réintervention pour GS positif est de l'ordre de 30 % s'il n'y a pas d'évaluation extemporane du GS, de 15 % si cette évaluation est faite par technique extemporane classique [6] voire bien moindre (nulle ?) avec les techniques d'évaluation moléculaire peropératoire du ganglion qui sont en train de se mettre en place [10].…”
Section: Intérêt Pour Les Patientes ?unclassified
“…. Pour le temps « pathologiste », l'arrivée de machines automatisées installées au bloc opératoire est une solution déjà mise en place aux États-Unis ou au Japon [10]. Le temps anesthésiste épargné est quant à lui plus discutable, peut-on en effet se passer de toutsurveillance anesthésique quand on sait qu'il peut y avoir des réactions anaphylactiques au bleu patenté ou lorsqu'il est nécessaire de compléter l'anesthésie locale ?…”
Section: Intérêt Organisationnel Et éConomique ?unclassified